Membangun Swadaya Free Open Source Editing Film Kdenlive Bagi Siswa Sekolah Menengah Kejuruan 1 Kabupaten Sorong - Waliulu, Raditya Faisal; Kahar, Muhammad Syahrul (Universitas Muhammadiyah Surabaya, 2018)
Acronym FOSS is a free open source software. The FOSS program is a license that allows users to run the program freely for any purpose, modify the program as desired and also distribute copies of the original version or modified version freely, which is why select open source from closed source. Closed-source software is sometimes pressed to build in the background or other unwanted and secret features into the software. Instead of having to trust users of FOSS software vendors can check and verify the source code itself and can put trust in the community of volunteers and users. FOSS is not equivalent to priceless software, it's more like a command for open-source software with freedom granted at various levels (depending on license). For this, the license does not need to be included in the list, If the software follows the Open Source command and the license is compatible then at least one of the Open Source licenses. Student involvement in SMK Negeri 1 Kabupaten Sorong is the best place to give advice about FOSS because it is one of the favorite schools in Sorong regency.